Severe microcephaly induced by blockade of vasoactive intestinal peptide function in the primitive neuroepithelium of the mouse. - Gressens, P (1994)
Vasoactive intestinal peptide (VIP) has potent growth-related actions that influence cell mitosis, neuronal survival, and neurodifferentiation in cell culture. VIP can also produce dramatic growth in postimplantation mouse embryos in vitro, characterized by large increases in cell number. The goal of the present study was to assess the role of VIP on early nervous system development in vivo. Pregnant mice were treated with a specific antagonist to VIP. Prenatal administration of the antagonist early in development (E9-E11) produced severe microcephaly characterized by decreased embryonic brain weight with reduced DNA and protein content. The retardation of growth was disproportionally manifested in the brain compared with the body and was prevented by co-treatment with VIP. Identical treatment with the antagonist later in gestation had no detectable effect on embryonic growth. VIP receptors, which were restricted to the central nervous system during this stage of embryonic development, were increased in the neuroepithelium of antagonist-treated embryos while the number of cells in S-phase was significantly decreased. Thus, VIP regulates brain growth in vivo and inhibition of its action provides new insight into a molecular mechanism for microcephaly.